Increasing Energy Efficiency With Entertainment Media: An Experimental and Field Test of the Influence of a Social Game on Performance of Energy Behaviors. (January 2015) - Reeves, Byron; Cummings, James J.; Scarborough, James K.; Yeykelis, Leo
Energy information for consumers can be complex and uninteresting. Games offer a compelling new context for home energy information that may engage consumers and change behaviors. Based on research showing the effectiveness of game elements used in serious contexts, we built a professional quality social game about energy use in a virtual home. In a laboratory experiment, playing the game for 30 min resulted in significant increases in energy efficient behaviors (e.g., turning off room lights) after play ended. In a field test of the same game, smart meter data showed a significant decrease in electricity usage compared with 30-day periods before and after play. Taken together, these results demonstrate that energy information embedded in an entertaining commercial-grade game can produce significant changes in energy behavior.